Dasatinib Attenuates Pressure Overload Induced Cardiac Fibrosis in a Murine Transverse Aortic Constriction Model - Balasubramanian, Sundaravadivel; Pleasant, Dorea L.; Kasiganesan, Harinath; Quinones, Lakeya; Zhang, Yuhua; Sundararaj, Kamala P.; Roche, Sandra; O’Connor, Robert; Bradshaw, Amy D.; Kuppuswamy, Dhandapani (PLOS ONE, 2015)
Reactive cardiac fibrosis resulting from chronic pressure overload (PO) compromises ventricular function and contributes to congestive heart failure. We explored whether nonreceptor tyrosine kinases (NTKs) play a key role in fibrosis by activating cardiac fibroblasts (CFb), and could potentially serve as a target to reduce PO-induced cardiac fibrosis. Our studies were carried out in PO mouse myocardium induced by transverse aortic constriction (TAC). Administration of a tyrosine kinase inhibitor, dasatinib, via an intraperitoneally implanted mini-osmotic pump at 0.44 mg/kg/day reduced PO-induced accumulation of extracellular matrix (ECM) proteins and improved left ventricular geometry and function. Furthermore, dasatinib treatment inhibited NTK activation (primarily Pyk2 and Fak) and reduced the level of FSP1 positive cells in the PO myocardium. In vitro studies using cultured mouse CFb showed that dasatinib treatment at 50 nM reduced: (i) extracellular accumulation of both collagen and fibronectin, (ii) both basal and PDGF-stimulated activation of Pyk2, (iii) nuclear accumulation of Ki67, SKP2 and histone-H2B and (iv) PDGF-stimulated CFb proliferation and migration. However, dasatinib did not affect cardiomyocyte morphologies in either the ventricular tissue after in vivo administration or in isolated cells after in vitro treatment. Mass spectrometric quantification of dasatinib in cultured cells indicated that the uptake of dasatinib by CFb was greater that that taken up by cardiomyocytes. Dasatinib treatment primarily suppressed PDGF but not insulin-stimulated signaling (Erk versus Akt activation) in both CFb and cardiomyocytes. These data indicate that dasatinib treatment at lower doses than that used in chemotherapy has the capacity to reduce hypertrophy-associated fibrosis and improve ventricular function.